A condition-based maintenance model considering multiple maintenance effects on the dependent failure processes. (April 2022) - Liu, Qiannan; Ma, Lin; Wang, Naichao; Chen, Ankang; Jiang, Qihang
Highlights: The soft failure due to system degradation and hard failure due to random shocks are dependent;. PM, CM and inspection are all negative or positive effect;. This effect is modeled by degradation level, deteriorate rate and hard failure threshold;. The effects of maintenance actions are intuitively described in a vector space;. The optimization model is established and the solving procedure is also given. Abstract: Maintenance is generally assumed to play a positive role, however, in reality, it is also common that maintenance actions have negative impacts. In this paper, a condition-based maintenance model for repairable systems subject to dependent failure processes (soft failure due to system degradation and hard failure due to random shocks) is proposed. It is a unified model with strong compatibility. The effects of maintenance actions with negative or positive effects incurred by inspection, preventive maintenance and corrective maintenance are all considered. In order to show the effects of maintenance actions intuitively, a vector space spanned by the degradation level, deteriorate rate and hard failure threshold is constructed. It can easily show the complex and multiple effects between maintenance impacts. Finally, the model is used to deal with high-voltage transmission lines' maintenance optimization problem. The results show that the model is feasible and can be applied in the field of maintenance optimization.